Banal Profundity and Profound Banality: Three Exercises in Reading Hong Kong. Issue 2 (June 2022) - Darius Nicholson, Rashna
Abstract : Focusing on performance that functions outside explicitly theatrical frames, art installations staged in Hong Kong between June and October 2020 progress a broader view of Hong Kong's complex development as global financial center, creative hub, and meeting point between "East" and "West." Artists Mark Chung, Nadim Abbas, and Christopher Ho interrogate Hong Kong at a historically definitive moment, allowing audiences to study what constitutes "home" beyond what conventional academic analyses, traditional publishing outlets, and social media allow.